Organochlorinated Pesticides and Health: Lessons for Parkinson’s Disease and Pesticides in General, and How to Heal it - Pirot, Florent (British Journal of Healthcare and Medical Research, 2025)
This article first provides the material explanation for the Chlordecone scandal, an organochlorinated pesticide that has been used largely until the 1990s. The diseases are explained from a chemo-physical principle that is related to the presence of alpha emitters from volcanic ashes associating with the negative ions chloride from the pesticides and bioaccumulating. It also allows to draw some more general conclusions on organochlorinated pesticides and health in general, and leads to general explanations on pesticides and Parkinson’s disease in particular, with the role of another channel, cation-fluoride, underlined. Lastly it is shown that magnetic acupuncture is able to heal it successfully.